Highly Enantioselective Synthesis of the 6-isopropyl-3,4-dihydropyrimidin-2-(1H)-thiones via Asymmetric Catalytic Biginelli Reactions - Hang, Zhijun; Dai, Guoyong; Yu, Han; Han, Sheng (Current Organic Chemistry, 2016)
In 1893, the synthesis of 3,4-dihydropyrimidin-2(1H)-ones via three-component condensation reaction of an aromatic aldehyde, urea and ethyl acetoacetate was reported for the first time by P. Biginelli. In the past century, such 3,4-dihydropyrimidin-2-(1H)-ones and related heterocyclic compounds have received a considerable amount of attention due to the interesting pharmacological properties associated with this heterocyclic scaffold. In particular, in recent twenty years, the synthesis of functionalized 3,4-dihydropyrimidin-2(1H)-ones have made great breakthrough. However, the asymmetric synthesis of functionalized 3,4-dihydropyrimidin-2(1H)-ones catalyzed by organocatalysts also is less. Furthermore, the 6-isopropyl dihydropyrimidines are very important intermediates for Statin drug. In this article, we mainly developed a simple and practical scheme for the synthesis of 6-isopropyl-3,4-dihydropyrimidines in a one-pot three-component condensation of aldehydes, β-dicarbonyl compounds, and thiourea via organocatalyzed asymmetric Biginelli reaction. Under the optimal reaction conditions, a series of desired products with remarkable pharmacological interest was obtained in high yields with excellent enantiomeric excess (up to 99% ee) using this practical method.
Keywords: chiral BINOL-derived phosphoric acid